GE_GERICHTE A/1075/2024 vom 4. August 2023 - GE Cour de justice (2023)
DÉTENTION AUX FINS D'EXPULSION;MESURE DE CONTRAINTE(DROIT DES ÉTRANGERS);MISE EN LIBERTÉ DÉFINITIVE | LEI.80.al5; LaLEtr.7.al4.letg; LEI.76.al1.letb